Le plurilinguisme dans le nouveau roman algérien de graphie française : quelles modalités linguistiques pour quels effets ? - Lamia HADJAB (Altralang Journal, 2023)
ABSTRACT: The new Algerian novel written in French is often marked by multilingualism, essentially due to contact with languages. This study tries to explore this literary plurilingualism in order to reveal the different modalities of its integration in the texts as well as the effects produced. Based on the linguistic analysis of some Algerian novels of French expression, plurilingualism appears mainly through borrowing and code-switching. The study of the different strategies for integrating these linguistic phenomena makes it possible to understand their effects on the understanding of the text.